EVALUATION OF ANTI-ULCER ACTIVITY OF THE ETHANOLIC EXTRACT OF PHYLLANTHUS URINARIA IN EXPERIMENTAL ANIMALS - Deshpande, Mangirish N; Balekar, Neelam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to investigate the antiulcer activity of the ethanolic extract of Phyllanthus urinaria (EEPU). Methods: In vivo anti-ulcer activity of EEPU was evaluated in the present study at 500 mg/kg body weight by pyloric ligation, ethanol-induced ulcer, aspirin-induced ulcer, and cold restraint-induced ulcer model. The anti-ulcer activity was assessed by determining and comparing the gastric volume, pH, free and total acidity, ulcer number and its inhibition, and ulcer severity. Result: EEPU at 500 mg/kg body weight dose showed significant antiulcer activity by decreasing ulcer index, gastric volume, pH, and free and total acidity. Gastroprotective effect of EEPU was substantiated by histopathological studies of the stomach in ulcer and treated groups. Conclusion: It can be concluded from the results that EEPU has potential antiulcer activity.